Light cured fluoride filled denture-coating materials - Kodkeaw,P. (John Wiley and Sons Inc., 2015)
Light cured denture-coating materials were prepared by formulating an acrylate monomer with a photoinitiator system (camphorquinone and dimethylaminoethyl methacrylate) using one of three base monomers [bisphenol A glycerolate diacrylate (Bis-GDA), glycerol 1, 3-diglycerolate diacrylate (GDA), and diurethane dimethacrylate (DU-DMA)] each with four diluents [triethylene glycol dimethacrylate (TEGDMA), di(ethylene glycol) methyl ether methacrylate, 2-hydroxyethyl methacrylate (HEMA), and methacrylic acid (MAA)] at a fixed 1 : 1 molar ratio of base monomer to diluent. The twelve formulations were then evaluated for their surface hardness and water sorption as coating materials. The DU-DMA/MAA, DU-DMA/HEMA, Bis-GDA/HEMA, and GDA/MAA based coatings provided a high level of both surface hardness and water sorption properties. When sodium fluoride (NaF) or calcium fluoride (CaF2) was incorporated into those formulations, the fluoride ion release rate from all four NaF containing coating materials was extremely high in the first week, decreasing sharply in the second week and then decreasing in the later 2 weeks. in contrast, the CaF2 containing coating materials showed a slower sustained rate of fluoride ion release over the 4-week test period, with the DU-DMA/HEMA based coating having a fluoride ion release pattern that meets the requirements for dental use. © 2009 Wiley Periodicals, Inc.